Impaired force control during food holding and biting in subjects with tooth- or implant-supported fixed prostheses - Svensson, Krister G.; Trulsson, Mats (Journal of clinical periodontology, 2011)
Aim Our goal here was to assess the ability of subjects with their natural teeth (natural), bimaxillary tooth‐supported bridges (bridge) and bimaxillary implant‐supported bridges (implant) to control the low contact and high biting forces associated with holding and splitting food between the teeth. Materials and Methods Ten subjects in each of these groups performed a task involving holding and splitting morsels of food with different degrees of hardness (biscuits and peanuts) between a pair of opposing central incisors. Results The hold force employed by the implant group was significantly higher and more variable than the corresponding force exerted by the bridge group, whereas the natural group used lowest and least variable force. For all three groups, the split force was higher and the split phase duration longer with peanuts than for biscuits. In the case of the natural group, a significantly higher rate of force increase (peak force rate) was observed when splitting peanuts when compared with biscuits, whereas no such difference could be seen for the other two groups. Conclusion These findings demonstrate that individuals with bimaxillary tooth‐ or implant‐supported bridges (in whom sensory information provided by the periodontal mechanoreceptors is impaired or missing) are unable to apply low‐hold forces at the levels of individuals with natural teeth or to adapt the rate of the split force to the hardness of the food. We thus conclude that adequate sensory information from periodontal mechanoreceptors is essential for normal control of both low contact and high biting forces.